Surfaceome and Proteosurfaceome in Parietal Monoderm Bacteria: Focus on Protein Cell-Surface Display - Desvaux, Mickaël; Candela, Thomas; Serror, Pascale (Frontiers in Microbiology, 2018)
The cell envelope of parietal monoderm bacteria (archetypal Gram-positive bacteria) is formed of a cytoplasmic membrane (CM) and a cell wall (CW). While the CM is composed of phospholipids, the CW is composed at least of peptidoglycan linked to other biopolymers, such as teichoic acids, polysaccharides and/or polyglutamate. Considering the CW is a porous structure with low selective permeability contrary to the CM, the bacterial cell surface hugs the molecular figure of the CW components as a well of the external side of the CM. While the surfaceome corresponds to the totality of the molecules found at the bacterial cell surface, the proteinaceous complement of the surfaceome is the proteosurfaceome. Once translocated across the CM, secreted proteins can either be released in the extracellular milieu or exposed at the cell surface by associating to the CM or the CW. Following the Gene Ontology (GO) for cellular components, cell-surface proteins at the CM can either be integral (GO: 0031226), i.e. the IMPs (integral membrane proteins), or anchored to the membrane (GO: 0046658), i.e. the lipoproteins. At the CW (GO: 0009275), cell-surface proteins can be covalently bound, i.e. the LPXTG-proteins, or bound through weak interactions to the peptidoglycan or wall polysaccharides, i.e. the cell-wall binding proteins. Besides monopolypeptides, some proteins can associate to each other to form supramolecular protein structures of high molecular weight, namely the S-layer, pili, flagella and cellulosomes. After reviewing the cell envelope components and the different molecular mechanisms involved in protein attachment to the cell envelope, perspectives in investigating the proteosurfaceome in parietal monoderm bacteria are further discussed.